Communication and Its Impact on Customer Satisfaction in Hospitality Industry - Andualem Walelign (iRASD Journal of Management)
The main aim of this study was to assess the influence of communication on customer satisfaction. Descriptive statistics (mean score and standard deviation) were used to examine the customers’ perceptions and current status of customer satisfaction. The least performance was obtained from the mean score of communication dimension. Correlation and regression analysis were used to see the relationship between dependent and independent variables as well as to investigate cause and effect relationships. The key finding showed that there was a positive and significant effect of communication on customer satisfaction.